Role of Pneumococcal NanA Neuraminidase Activity in Peripheral Blood - Syed, Shahan; Hakala, Pipsa; Singh, Anirudh K.; Lapatto, Helena A. K.; King, Samantha J.; Meri, Seppo; Jokiranta, T. Sakari; Haapasalo, Karita (Frontiers in Cellular and Infection Microbiology, 2019)
The most frequent form of hemolytic-uremic syndrome (HUS) is associated with infections caused by Shiga-like toxin-producing Enterohaemorrhagic Escherichia coli (STEC). In rarer cases HUS can be triggered by Streptococcus pneumoniae. While production of Shiga-like toxins explains STEC-HUS, the mechanisms of pneumococcal HUS are less well-known. S. pneumoniae produces neuraminidases with activity against cell surface sialic acids that are critical for factor H-mediated complement regulation on cells and platelets. The aim of this study was to find out whether S. pneumoniae neuraminidase NanA could trigger complement activation and hemolysis in whole blood. We studied clinical S. pneumoniae isolates and two laboratory strains, a wild-type strain expressing NanA, and a NanA deletion mutant for their ability to remove sialic acids from various human cells and platelets. Red blood cell lysis and activation of complement was measured ex vivo by incubating whole blood with bacterial culture supernatants. We show here that NanA expressing S. pneumoniae strains and isolates are able to remove sialic acids from cells, and platelets. Removal of sialic acids by NanA increased complement activity in whole blood, while absence of NanA blocked complement triggering and hemolytic activity indicating that removal of sialic acids by NanA could potentially trigger pHUS.